Fede cristiana, devozione mariana e pandemia da covid-19. Il “caso” della comunità di Biancavilla (Ct) - Ciarocchi, Valerio (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The crisis dramatically resulting from the sudden pandemic for Covid-19 had immediate and long-term consequences. From a religious point of view, what were the answers? The civil and ecclesial community of Biancavilla country is unique in the Etna province and in Valdemone, since it is the only one of Arbëreshë origin, although now Latinized, arrived and finally settled at the foot of Etna, after the exile following the fall of Byzantium. The exiles brought with them an icon of the Mary of almsgiving, which is to some extent at the origin of the foundation of the town. The local historical, social and religious history is linked to the cult, first Byzantine, then Latin, of the Virgin of Mercy, and its icon. The people of Biancavilla country have always devoted their devotion to it, especially on the occasion of wars, famines, plagues, obtaining, according to the faith of the people, the favor of the Virgin, despite the fact that neighboring communities were equally affected. We want to report the “case” of the Biancavilla community, which faced the health emergency caused by Covid-19, also from a religious point of view with a constant, broad, varied commitment, not only liturgical or devotional, but also educational. Expressing once again its Christian faith in devotion to the Virgin of Alms, her patron. While the commitment of the clergy to a constant liturgical and pastoral activity has not been lacking, the faithful also maintained the oratorio and educational activities through the use of the internet, using all the communication channels available, with positive results also with respect to other civil and religious communities, during the long period of isolation, keeping personal and community relationships alive. The biancavillese marian devotion therefore permeated and acted as an agglutinant of the overall estate of the small town of Biancavilla.